Prevalence of abdominal obesity in adolescents: association between sociodemographic factors and lifestyle - Castro,João Antônio Chula (2016)
Abstract Objective: To estimate the prevalence of abdominal obesity and verify the association with sociodemographic factors (gender, school shift, ethnicity, age, maternal education and economic status) and lifestyle (alcohol consumption, sleep, soft drink consumption, level of physical activity and sedentary behavior) in adolescents in Southern Brazil. Methods: This was a cross-sectional epidemiological study of 930 adolescents (490 girls) aged 14–19 years, living in the city of São José, SC, Brazil. A self-administered questionnaire was used to collect sociodemographic and lifestyle data. Abdominal obesity was measured through the waist circumference and analyzed according to gender and age. Descriptive statistics (absolute and relative frequency, mean and standard deviation) and binary logistic regression, expressed as Odds Ratios (OR) and 95% confidence interval (95%CI) were employed, with p<0.05 being considered statistically significant; the SPSS 17.0 software was used for the statistical analyses. Results: The prevalence of abdominal obesity was 10.6% for the total sample (10.5% male, 10.8% female). Adolescents that watched television daily for two or more hours (OR=2.11, 95%CI 1.08–4.13) had a higher chance of having abdominal obesity and adolescents whose mothers had fewer than eight years of schooling (OR=0.56; 95%CI from 0.35 to 0.91) had a lower chance of having abdominal obesity. Conclusions: Approximately one in 10 adolescents had abdominal obesity; the associated factors were maternal schooling (≥8 years) and television screen time (≥2h/day).